Resetting amino acid metabolism of cancer cells by ATB0,+-targeted nanoparticles for enhanced anticancer therapy - Longfa Kou; Xinyu Jiang; Yingying Tang; Xing Xia; Yingtao Li; Aimin Cai; Hailun Zheng; Hailin Zhang; Vadivel Ganapathy; Qing Yao; Ruijie Chen (Bioactive Materials, 2022)
Reprogramed cellular metabolism is one of the most significant hallmarks of cancer. All cancer cells exhibit increased demand for specific amino acids, and become dependent on either an exogenous supply or upregulated de novo synthesis. The resultant enhanced availability of amino acids supports the reprogramed metabolic pathways and fuels the malignant growth and metastasis of cancers by providing energy and critical metabolic intermediates, facilitating anabolism, and activating signaling networks related to cell proliferation and growth. Therefore, pharmacologic blockade of amino acid entry into cancer cells is likely to have a detrimental effect on cancer cell growth. Here we developed a nanoplatform (LJ@Trp-NPs) to therapeutically target two transporters, SLC6A14 (ATB0,+) and SLC7A5 (LAT1), that are known to be essential for the sustenance of amino acid metabolism in most cancers. The LJ@Trp-NPs uses tryptophan to guide SLC6A14-targeted delivery of JPH203, a high-affinity inhibitor of SLC7A5. In the process, SLC6A14 is also down-regulated. We tested the ability of this strategy to synergize with the anticancer efficacy of lapatinib, an inhibitor of EGFR/HER1/HER2-assocated kinase. These studies show that blockade of amino acid entry amplifies the anticancer effect of lapatinib via interference with mTOR signaling, promotion of apoptosis, and suppression of cell proliferation and metastasis. This represents the first study to evaluate the impact of amino acid starvation on the anticancer efficacy of widely used kinase inhibitor.